2015
DOI: 10.1177/1541931215591322
|View full text |Cite
|
Sign up to set email alerts
|

Specific Evacuation Instructions Enhance Spoken Fire Warnings

Abstract: Most building fire alarms are presented auditorily and almost all are simple non-verbal sounds, such as bells and buzzers-despite the availability of inexpensive, feasible, voice-presentation technology. One advantage of speech or vocal signals is that they can convey specific avoidance instructions. This study examined the content (wording) of spoken fire alarms. Sixty-five participants rated 90 spoken fire evacuation warnings plus two non-speech sounds (white noise and a recording of an actual [simple, nonve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, the ISO evacuation signal norm (see parameters in ISO 8201: 2017) only required a simple T‐3 pattern transmitted through a single auditory modality. There is an optional choice of the supplementary speech specified by the ISO 8201: 2017 norm and researchers have suggested that the presence of a speech warning produces a strong and reliable increase in compliance compared with conditions without a speech warning (Taylor & Wogalter, 2015; Wogalter & Conzola, 2002). Nevertheless, they should validate this effect on the ISO evacuation signal considering the pre‐emergency period.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ISO evacuation signal norm (see parameters in ISO 8201: 2017) only required a simple T‐3 pattern transmitted through a single auditory modality. There is an optional choice of the supplementary speech specified by the ISO 8201: 2017 norm and researchers have suggested that the presence of a speech warning produces a strong and reliable increase in compliance compared with conditions without a speech warning (Taylor & Wogalter, 2015; Wogalter & Conzola, 2002). Nevertheless, they should validate this effect on the ISO evacuation signal considering the pre‐emergency period.…”
Section: Introductionmentioning
confidence: 99%